An Empirical Analysis of Liquidity Risk and Performance in Malaysia Banks - Abdul Rahman, Nora Azureen; Saeed, Maytham Hussein (INSInet Publications, 2015)
The nature of banking business exposed banks to various risks which culminate in the form of liquidity risks. Banks with high liquidity risk may face difficulties in fulfilling its financial obligation to the customers, extending their business and eventually may affect the overall performance of the bank. Understanding the critical effects of liquidity risk, this study aimed at examining the liquidity risk exposure of Malaysian banks and its effects on the banks’ performance. It is hypothesized that high liquidity risk will decrease the bank performance. This study used three liquidity risk indicators and the study period is confined to 2005-2013. The results suggest that the Malaysian banks do not involve in excessive lending, have a reasonable level of liquid assets and good capital standing. However, the regression results revealed that not all of the liquidity risk indicators affect the banks’ performance. Loan to deposit ratio has no significant effects on changes in the bank's performance, liquid asset to total assets imposed opportunity costs to the banks while capital to asset ratio provide mixed results with the performance measures. Overall, the regression results show that the effects of liquidity risk on Malaysian banks’ performance are not clear-cut, and varies with the performance measures used.